Islamization of Science: Ziauddin Sardar’s Critique of the Universality of Science - Putawa, Rilliandi Arindra (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This qualitative research explores Ziauddin Sardar's critique of Western-influenced universal science. It employs a literature study to analyze Sardar's thoughts using various methods. The findings reveal that Islamic science, rooted in ethical principles, offers an alternative to Western science, which often overlooks diverse paradigms and local knowledge systems. While Islamic science excels in addressing region-specific issues, it may struggle with complex problems. In contrast, Western science, considered global, has historically caused environmental challenges by disregarding non-conventional paradigms. Therefore, Islamic science, with its inclusive approach to knowledge, presents a potential solution to the crises stemming from the dominance of Western scientific paradigms.